The links between philosophy and sociology - Hilde Sánchez Morales; Morales Arias, Rosario (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This text focuses on the genesis of the social sciences through an analytical-descriptive about the systematization of science. Science is a creation of human beings and constitutes the best tool to acquire knowledge about your environment, yourself, the universe... It must be interdisciplinary and to support this endeavor, we have had to choose, and we have chosen to compare sociology with philosophy looking for contributions (implicit or explicit) of prestigious thinkers.
Keywords: philosophy; sociology; social sciences; systematization of science